Towards (Hyper)Local Public Sphere: Comparison of Civic Engagement across the Global North - Hujanen, Jaana; Dovbysh, Olga; Jangdal, Lottie; Lehtisaari, Katja (Media and Communication, 2022)
The role of hyperlocal media is of increasing relevance as traditional local journalism experiences a decline due to centralisation and consolidation. The affordances of Internet and digital technologies also enable hyperlocal initiatives to enhance civic engagement in localities and serve as a place and resource for local deliberative processes. This study examines how the aims, perceptions and practices of hyperlocal media vary in three countries of the Global North - Sweden, Finland and Russia - and what implications this has for connectedness and civic engagement in local public spheres. The context of different media systems and local political regimes help to explore possibilities and limitations of hyperlocals as agents of place-oriented civic engagement. The data includes interviews with practitioners and analysis of selected hyperlocal media. Our results indicate that hyperlocal media practitioners in all three countries aim to provide local people and communities with a voice, and to enhance resident engagement in local life. We reveal three civic roles of hyperlocal media: (i) information provider, (ii) community builder, and (iii) civic mediator. Practices of civic engagement used by hyperlocal media range from relying on civic journalism to fostering civic debates and can be classified in two main categories: civic information and civic debate and interaction. The perceptions and practices of these hyperlocal media are, to some extent, similar because of comparable changes and challenges regarding the local media and public spheres. At the same time, the perceptions of civic roles vary, reflecting both the developments and differences in the countries' media spheres and political regimes. This research raises a critical question about hyperlocal practitioners' understanding of their own roles and aims, and in addition, how differences in media cultures and local regimes affect their performance as agents of local public spheres.